Pertumbuhan stek batang kantong semar (Nepenthes bicalcarata Hooker) dengan penambahan Indole Butyric Acid (IBA) - Riza Linda, Sutria Ningsih, Mukarlina, (Universitas Tanjungpura, 2014)
Nepenthes bicalcarata commonly grows in the edge of swampy mangrove forest and heath forest which are poor in nutrients and have a relatively high humidity. The conservation effort on N. bicalcarata can be done through plant multiplication by stem cuttings. This study aims to determine the effect of indole butyric acid (IBA) growth regulator addition on the growth of N. bicalcarata stem cuttings and to determine the concentration of IBA growth regulator that can give the best growth on N. Bicalcarata stem cuttings. The study was conducted in November 2013 to February 2014. Based on ANOVA analysis, the addition of IBA on N. bicalcarata stem cuttings significantly affected the height of the plant and the number of roots. The best IBA concentration given on N. bicalcarata stem cuttings was at 15 ppm, resulting in 19,50 cm of average plant heights and 27,25 of average roots number. The addition of IBA did not significantly affect the number of leaves and initial budding period.